Pre-meiotic transformation of germplasm-related structures during male gamete differentiation in Xenopus laevis. Issue 1 (16th December 2014) - Reunov, Arkadiy A.; Reunova, Yulia A.
Summary: To highlight the ultrastructural features of transformation occurring with germplasm-related structures (GPRS), the spermatogenic cells of Xenopus laevis were studied by transmission electron microscopy and quantitative analysis. It was determined that in spermatogonia and spermatocytes, the compact germinal granules underwent fragmentation into particles comparable with inter-mitochondrial cement (IMC). Fragments of IMC agglutinated some cell mitochondria and resulted in the creation of mitochondrial clusters. Clustered mitochondria responded with loss of their membranes that occurred by the twisting of membranous protrusions around themselves until multi-layered membranes were formed. The mitochondrial affinity of multi-layered membranes was proven by an immunopositive test for mitochondrial dihydrolipoamide acetyltransferase. As a consequence of mitochondrial membrane twisting, the naked mitochondrial cores appeared and presumably underwent dispersion, which is the terminal stage of GPRS transformation. As no GPRS were observed in spermatids and sperm, it was assumed that these structures are functionally assigned to early stages of meiotic differentiation.